Research on Hybrid Real-Time System Scheduling Algorithm for Multiprocessor Environment - Cai Ren, Pu Cuo; Hong, JianChao (Journal of physics. Conference series, 2021)
Firstly, the mixed key system task model of compatible with periodic tasks and sporadic tasks is studied. Based on the model compatible with these two tasks, a semi-divided real-time task scheduling mechanism is proposed. This process also considers the aggressive handling of Low critical task to improve resource utilization. Finally, the relevant program code is designed and developed, and the performance of the proposed algorithm is evaluated by means of simulation and simulation. The correctness of the model and theory is verified, and the theory and protocol design are further improved.